Interaction between nestling behaviour and nest-space use. Issue 5 (3rd September 2021) - Nuhlíčková, Soňa; Svetlík, Ján; Eckenfellner, Manfred; Knauer, Felix; Hoi, Herbert
Abstract : For most animals, the rearing environment is an important factor influencing early offspring development and behaviour. Also, in altricial birds, where the rearing environment (nest) is usually restricted, it is known that if sufficient nest space is provided, offspring show social interactions and a variety of other behaviours. In fact, the available nest space has been identified as an important determinant for the occurrence or outcome of social interactions. In this context, we predict different behaviours like food acquisition, intra-brood competition, comfort behaviour or defecation activities also happen at specific sites within the nest and allow differential nest-space use. We further predict, that even offspring within a brood may differently experience their rearing environment. In line with this, e.g. nestling age, brood size or parental food allocation rules could be influential factors. In this study, we therefore investigated offspring nest-space use in altricial hoopoe nestlings ( Upupa epops ) raised in spacious nest boxes. In particular, we focused on nest-space use in relation to four major offspring behaviours, namely successful food acquisition, aggressive interactions, comfort and resting behaviour and defecation, additionally including parental feeding strategy (feeding from inside or outside the nest box), nestling age and brood size as potentially influential factors. Our results reveal that nestlings do not use the nest space equally but use specific locations for different purposes. Our results further suggest that beside behaviour also offspring age, brood size and parental feeding strategy influence their nest-space use. In conclusion, differential nest-space use can occur even in nestlings and already at an early age. Thus, nest space seems to be an important nest quality feature determining not only nest-space use but also affects offspring social interactions.